2016
DOI: 10.1038/srep36639
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of breast cancer in Lebanese women

Abstract: Breast cancer is commonest cancer in women worldwide. Elucidation of underlying biology and molecular pathways is necessary for improving therapeutic options and clinical outcomes. Molecular alterations in breast cancer are complex and involve cross-talk between multiple signaling pathways. The aim of this study is to extract a unique mRNA fingerprint of breast cancer in Lebanese women using microarray technologies. Gene-expression profiles of 94 fresh breast tissue samples (84 cancerous/10 non-tumor adjacent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 60 publications
1
27
0
Order By: Relevance
“…COL10A1 protein levels in plasma might be a potential diagnostic predictor for early breast cancer [9]. Although COL10A1 was reported to be highly expressed in tumors by high throughput sequencing, the specific role of COL10A1 in breast cancer was unknown [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…COL10A1 protein levels in plasma might be a potential diagnostic predictor for early breast cancer [9]. Although COL10A1 was reported to be highly expressed in tumors by high throughput sequencing, the specific role of COL10A1 in breast cancer was unknown [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The disruption on (or resistance to) the action of leptin is a hallmark of obesity, which in turn is a strong risk factor for several diseases including diabetes, cardiovascular disease, and certain types of cancers [ 29 ]. Recently, two independent studies reported that LEP was among the most down-regulated genes in breast cancers of Lebanese [ 30 ] and Saudi Arabian cohorts [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, it is largely unknown how collagen type VI α4, α5 and α6 are implicated in tumor development. COL6A6 has been reported to be down-regulated in breast cancer [27][28][29] . Significant down-regulation of COL6A5 has been proved in esophageal squamous cell carcinoma 30 and fibrous epulis 31 .…”
Section: Discussionmentioning
confidence: 99%